2021
DOI: 10.26444/aaem/120927
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance of <i>Escherichia coli</i> and <i>Klebsiella</i> spp. conventionally sampled from factory-farmed chickens – clinical submissions

Abstract: Introduction. The article discusses the antimicrobial resistance of poultry-isolated bacteria in the Wielkopolska region of Poland. Materials and method. From August 2014 -June 2016, antibiotic resistance screening tests were performed involving 4,496 samples of Escherichia coli and 84 samples of Klebsiella spp., and the following antibiotics: amoxicillin, amoxicillin with clavulanic acid, colistin, doxycycline, enrofloxacin, florfenicol, neomycin, norfloxacin, spectinomycin, and trimethoprim with sulfamethoxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…isolated from turkeys ( Table 1 ). This is in line with the findings made by Majewski et al [ 28 ], who additionally reported similar susceptibility to trimethoprim-potentiated sulphonamides as a characteristic of approx. 70% of Klebsiella spp.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…isolated from turkeys ( Table 1 ). This is in line with the findings made by Majewski et al [ 28 ], who additionally reported similar susceptibility to trimethoprim-potentiated sulphonamides as a characteristic of approx. 70% of Klebsiella spp.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings only diverge with respect to Klebsiella spp. susceptibility to florfenicol and amoxicillin/clavulanic acid in our own study, over 80% of the isolates exhibited antibiotic sensitivity ( Table 1 ), whereas Majewski et al [ 28 ] found only 10% and 38% of the strains to be sensitive to the two antimicrobials, respectively. It should be noted that the study by Majewski et al [ 21 ] concerned Klebsiella spp.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…Similar data across experimental and control chicken groups were obtained for spectinomycin and florfenicol, where the values were 40% in the experimental group vs. 39.087% and 40% vs. 38.15%, respectively. A total of 60% of the isolates in both groups were classified as moderately susceptible to spectinomycin, 4% in the experimental group vs. 3.83% to norfloxacin, 24% vs. 44.16% to florfenicol, 52% vs. 11.89% to doxycycline, and 28% vs. 9.75% to amoxicillin with clavulanic acid (14).…”
Section: Discussionmentioning
confidence: 99%